Wantok and Lain ‐ a look at two Melanesian cultural concepts in two Tok Pisin texts. Issue 2 (1st October 2019) - Kornacki, Paweł
AbstractThis article looks at salient interpersonal uses and meanings of two prominent Tok Pisin social relations nouns ‐ wantok ('friend', 'same language speaker') and lain ('group', 'family', 'clan') ‐ which it is proposed exemplify key cultural Melanesian concepts in some anthropological literature of the area. Whereas certain aspects of language use in Tok Pisin were identified as potentially divisive and socially harmful, some scholars endeavoured to identify a group of concepts indicative of culturally specific Melanesian values. For example, the words wantok and lain were claimed to jointly represent 'the value of the clan' across Melanesian societies, while embodying and supporting a distinct world-view of the Melanesian peoples. This article studies two Tok Pisin texts which focus on the cultural significance of concepts of wantok and lain in their rural/traditional environment. While the first text offers a native speaker's insight into the social significance of the cultural expression wantok sistem ('system favouring friends'), the other one details the roles of lain in the passage of a bride-price ceremony. Given that both texts presuppose the cultural background of rural Tok Pisin, a brief look at some characteristic usage of the two words in electronic media suggests that certain aspects of traditional uses and meanings of these words may be extended and employed to conceptualize new social and political phenomena.